Features on students empathy development in Medical College (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. Anxiety, preoccupation, immaturity, and self-absorption preventus from empathizing with other people. During two years the sufficientamount of students and teachers of medical college were analyzed, todo an encouraging conclusion that a level of empathy is at low level.Does a medical worker need to be a person with a high level of empathyor will this human quality only interfere with his professional duty? Theimportant point is about that we must always remember the basis of medicalhumanism is the universal human moral standards, clearly formulated bymedical ethics and medical deontology. One of such norms is responsiveattitude toward pain, suffering and illness of another person.
Keywords: «Culture of Empathy»; intuition; affective sensitivity; identification; empathy; emotional intelligence; deontology